Selective molecular annealing: in situ small angle X-ray scattering study of microwave-assisted annealing of block copolymers. Issue 31 (21st July 2017) - Toolan, Daniel T. W.; Adlington, Kevin; Isakova, Anna; Kalamiotis, Alexis; Mokarian-Tabari, Parvaneh; Dimitrakis, Georgios; Dodds, Christopher; Arnold, Thomas; Terrill, Nick J.; Bras, Wim; Hermida Merino, Daniel; Topham, Paul D.; et al.
Abstract : A new experimental set-up facilitating in situ SAXS during microwave annealing of polymers. Abstract : Microwave annealing has emerged as an alternative to traditional thermal annealing approaches for optimising block copolymer self-assembly. A novel sample environment enabling small angle X-ray scattering to be performed in situ during microwave annealing is demonstrated, which has enabled, for the first time, the direct study of the effects of microwave annealing upon the self-assembly behavior of a model, commercial triblock copolymer system [polystyrene- block -poly(ethylene- co -butylene)- block -polystyrene]. Results show that the block copolymer is a poor microwave absorber, resulting in no change in the block copolymer morphology upon application of microwave energy. The block copolymer species may only indirectly interact with the microwave energy when a small molecule microwave-interactive species [diethylene glycol dibenzoate (DEGDB)] is incorporated directly into the polymer matrix. Then significant morphological development is observed at DEGDB loadings ≥6 wt%. Through spatial localisation of the microwave-interactive species, we demonstrate targeted annealing of specific regions of a multi-component system, opening routes for the development of "smart" manufacturing methodologies.